Technology Supported Geriatric Assessment - Hellmers, Sandra; Fudickar, Sebastian; Büse, Clemens; Dasenbrock, Lena; Heinks, Andrea; Bauer, Jürgen M; Hein, Andreas (Ambient Assisted Living: 9. AAL-Kongress, Frankfurt/M, Germany, April 20 - 21, 2016, 2017)
Healthy aging is a core societal aim especially regarding the demographic change. But with aging, functional decline can occur and this is a major challenge for health care systems. For the evaluation of the health of older adults and the identification of early changes associated with functional and cognitive decline, clinical geriatric assessments are a well-established approach. Ideally, the assessments should take place at home of the older adults or even in their daily life, to get an unbiased functional status. Therefore, we introduce a technology supported geriatric assessment as an intermediate step to a home-assessment or in future to sensor-based-assessments in daily life. Beside various ambient sensors, a sensor belt is used during the assessments and for 1 week in the participants' daily life. We discuss the suitability of our measuring devices for an ambient home-assessment and evaluate the sensors in comparison to valid measurements. Thereby, we show that light barrier measurements achieve a high sensitivity and a good correlation to manual measurements through study nurses or physical therapists.